8-Methyladenosine-substituted analogues of 2-5A: synthesis and their biological activities. - Kitade, Y (1991)
8-Methyladenosine-substituted analogues of 2-5A, p5'A2'p5'A2'p5'(me8A), p5'A2'p5'(me8A)2'p5'(me8A), p5'(me8A)2'p5'(me8A)2'p5'(me8A), and p5'(me8A) 2'p5'A2'p5'A, were prepared via a modification of a lead ion-catalyzed ligation reaction. These 2-5A monophosphates were converted into the corresponding 5'-triphosphates. Substitution of an 8-methyladenosine residue at the third position (2'-terminus) of the oligonucleotides increased the stability to snake venom phosphodiesterase digestion. Both binding and activation of mouse liver 2-5A dependent ribonuclease (RNase L) by the various 8-methyladenosine-substituted 2-5A analogues were examined. Among the 8-methyladenosine-substituted trimer analogues, the analogues with 8-methyladenosine residing in the 2'-terminal position showed the strongest binding affinity and were several times more effective than 2-5A itself as an inhibitor of translation.